Waste not, want not: Europe's untapped potential to generate valuable negative emissions from waste-to-energy (WtE) using carbon capture technology - Hasan Muslemani; Iain Struthers; Laura Herraiz; Camilla Thomson; Mathieu Lucquiaud (The Oxford Institute for Energy Studies, 2023)
Waste-to-energy (WtE) is a waste treatment process that incinerates waste to produce energy in the form of electricity and/or heat. WtE is considered one of the most environmentally-friendly methods of dealing with residual waste. The alternative to this process is waste dumping or landfilling, both of which lead to long-term adverse impacts on the environment. The capture of CO2 from WtE plants has received increasing attention over the past decade. Particularly, waste contains a substantial amount of biogenic carbon content (i.e., carbon which is naturally part of the carbon cycle), the capture and permanent removal of which leads to 'negative emissions'. Considering the important role of carbon-negative solutions in achieving ambitious decarbonisation goals, retrofitting WtE plants with carbon capture and storage (CCS) will be a major starting point. This study assesses the potential for generating negative emissions from the European WtE fleet by assessing its retrofitability with CCS based on a number of criteria: i) an acceptable distance for CO2 transport between WtE plants and CCS clusters, hubs and CO2 storage sites, ii) availability of on-site space for CCS retrofit at the plant level, and iii) an appropriate plant size to ensure that CO2 capture is economically viable. Results show that if the entire existing European WtE fleet was retrofitted with CCS (around 100Mt of installed capacity), negative emissions in the range of -50.5 to - 70.6 MtCO2 can be generated per year. When CCS limitations are taken into account, these estimates are naturally reduced, with an achievable range between -20 to -30 MtCO2/a. Note that if waste that is currently mismanaged and/or is going to landfill is instead redirected towards WtE+CCS, higher negative emissions can be captured depending on the evolution of future waste management policies in Europe.
Keywords: 330; carbon capture; Carbon Capture and Storage; carbon removal; CCS; Climate Action; negative emissions; waste management; waste to energy